Despesas de exercícios anteriores e o limite de gasto com pessoal em Minas Gerais - 2007 a 2018 - Lopes, Rosemary Miranda Mattos Ferreira (2019)
The occurrence of Previous Fiscal year’ Expenses (PFE) and the evolution of personnel expenses in the Brazilian states, especially in Minas Gerais (MG), in recent years, are the current issues of discussion that give rise to confrontation in the academic community. This perception arises from a question that motivates the present study: what is the behavior of the PFE in the accomplishment of the personal spending limit in MG from 2007 to 2018? The general objective of this research is to understand PFE’s behavior regarding personnel spending limit, specifically: (i) describe the evolution of PFE concerning Net Current Revenue (NCR), Personnel Gross Expense (PGE) and Personnel Net Expense (PNE); (ii) identify the behavior of the PFE related to the personal spending limit in the state; and (iii) propose an action protocol with the purpose to identify and interpret PFE's share of personnel expenses. Within twelve years, the units researched were the three State Powers - Executive, Legislative and Judiciary - and the organs - Public Prosecutor and Court of Auditors. The theoretical discussion was based on two perspectives: the first, under the constitutional based legal-normative approach; and the second, under the technicalfiscal aspect implemented with the advent of the Fiscal Responsibility Law (FRL). The approach of this study is predominantly quantitative and the finality is exploratory and descriptive. The method of the research is collection and the data collection technique is documentary research. The analysis of the results consisted on the application of descriptive statistics. The survey results demonstrate the evolution of personnel expenses, a spare of PGE over NCR, and show the continuous evolution of PFE in the state in detriment of the NCR growth. The results show the existence of investigated units that are guided by the exceptional use of the PFE records, meanwhile others register increasingly. The methodological divergence, for the purpose of calculating the personnel spending limits in the state, was shown as a favorable point to the fulfillment of the FRL. The PFE behavior of the units under study was differently revealed. The calculation simulation, with and without the deduction of the PFE from the PGE, demonstrated a comparative situation of overspending possibility. Examination of the PFE registry, following the adoption of the PFE’s participation indicator over the PGE and PNE, is a description of the repercussion of its incidence on personnel expenses. Considering the analysis of the dynamics among NCR, PGE, PNE and PFE, its suggested an intervention proposal consistent with an action protocol based on two action matrices from which emerge the PFE follow-up action plan. It is proposed to adopt the PFE’s participation indicator as a tool for perception of the incidence of evolution in the PFE in personnel expenses. The PFE’s incidence level of records configure a participation indicator of the PFE categorization. A proposed intervention is characterized as a PFE follow-up tool included in the group of personnel expense and social charges. This proposal represents an important instrument for identifying, interpreting, monitoring and retaining personnel expenses concerning past fiscal years that were not planned in the budget.